DFT Study on Regulating the Electronic Structure and CO2 Reduction Reaction in BiOBr/Sulphur-Doped G-C3N4 S-Scheme Heterojunctions - Fei, Xingang; Zhang, Liuyang; Yu, Jiaguo; Zhu, Bicheng (Frontiers in Nanotechnology, 2021)
Photocatalytic CO2 reduction is a promising method to mitigate the greenhouse effect and energy shortage problem. Development of effective photocatalysts is vital in achieving high photocatalytic activity. Herein, the S-scheme heterojunctions composed by BiOBr and g-C3N4 with or without S doping are thoroughly investigated for CO2 reduction by density functional theory (DFT) calculation. Work function and charge density difference demonstrate the existence of built-in electric field in the system, which contributes to the separation of photogenerated electron-hole pairs. Enhanced strength of built-in electric field is revealed by analysis of Bader charge and electric field intensity. The results indicate that S doping can tailor the electronic structures and thus improve the photocatalytic activity. According to the change in absorption coefficient, systems doping can also endow the heterojunction with increased visible light absorption. The in-depth investigation indicates that the superior CO2 reduction activity is ascribed to low rate-determining energy. And both of the two heterojunctions are inclined to generate CH3OH rather than CH4. Furthermore, S doping can further reduce the energy from 1.23 eV to 0.44 eV, indicating S doping is predicted to be an efficient photocatalyst for reducing CO2 into CH3OH. Therefore, this paper provides theoretical basis for designing appropriate catalysts through element doping and heterojunction construction.